2021
DOI: 10.1007/s10126-021-10020-z
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetically Controlled Spirulina, but Not Solar Spirulina, Inhibits TNF-α Secretion: Potential Implications for COVID-19-Related Cytokine Storm Therapy

Abstract: An array of infections, including the novel coronavirus (SARS-CoV-2), trigger macrophage activation syndrome (MAS) and subsequently hypercytokinemia, commonly referred to as a cytokine storm (CS). It is postulated that CS is mainly responsible for critical COVID-19 cases, including acute respiratory distress syndrome (ARDS). Recognizing the therapeutic potential of Spirulina blue-green algae (Arthrospira platensis), in this in vitro stimulation study, LPS-activated macrophages and monocytes were treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The presence of these molecules indicates its potential role in resistance to infection and progression of the COVID-19 disease. Such cyanobacteria-based nutraceuticals could be used as immune boosters to fight the human coronavirus and other viral diseases in association with vaccines [ 122 ]. The spike protein of severe acute respiratory syndrome due to COVID-19 uses angiotensin-converting enzyme 2 as the receptor for cell entry, which is highly expressed in the gut and lungs.…”
Section: Applications In Covid-19 Infectionmentioning
confidence: 99%
“…The presence of these molecules indicates its potential role in resistance to infection and progression of the COVID-19 disease. Such cyanobacteria-based nutraceuticals could be used as immune boosters to fight the human coronavirus and other viral diseases in association with vaccines [ 122 ]. The spike protein of severe acute respiratory syndrome due to COVID-19 uses angiotensin-converting enzyme 2 as the receptor for cell entry, which is highly expressed in the gut and lungs.…”
Section: Applications In Covid-19 Infectionmentioning
confidence: 99%
“…Recently, the overexploitation of the natural resource with antiviral substances has received more attention. There are numerous researches that recommended the antiviral activity of algal substances such as seaweed polysaccharides (Chi et al 2020 ; Diogo et al 2015 ; Elizondo-Gonzalez et al 2012 ; Gomaa and Elshoubaky 2016 ), phlorotannins (Park et al 2013 ), cyanovirin-N (Rui et al 2008 ), proteins such as lectin (Hwang et al 2020 ; Lee 2019 ; Mu et al 2017 ), phycobiliproteins (Abd El Hamid et al 2019 ), and cyanobacteria such as Spirulina with the potential of using for stimulating the immune system and acting as antivirus against COVID-19 by inhibition of TNF-α secretion during cytokine storm therapy (El-Sheekh and Abomohra 2020 ; Singh et al 2020 ; Tzachor et al 2021 ). There is little information about the anti-COVID 19 activity of the other algal bioactive compounds.…”
Section: Algae As a Source Of Anti-viral Bioactive Compoundsmentioning
confidence: 99%
“…Other than antiviral agents, algal nutraceuticals with their anti-inflammatory, antimicrobial, immunostimulatory, and immunomodulatory properties are also important for boosting immunity, preventing diseases and treating disorders associated with the severe SARS-CoV-2 infections, such as anti-inflammatory treatment and tissue repair [ 23 ]. For instance, C-phycoyanin, a pigment-binding protein, with the properties of anti-inflammation, antioxidation, and anti-tumor was tested to reduce the secretion levels of a protein, which causes cytokine storms in COVID-19 patients [ 21 ]. Although it will not replace SARS-CoV-2 vaccinations, the algae extract may be used a dietary supplement to prevent cytokine storms once the patients are diagnosed, especially those high-risk populations including the elderly and those with severe medical conditions [ 24 ].…”
Section: Potential Of Microalgal Value-added Productsmentioning
confidence: 99%
“…On the other hand, C-phycocyanin, a pigment-binding protein found in Spirulina blue-green algae, enhances anti-tumor, anti-inflammation, and antioxidation activities [ 20 ]. Tzachor et al [ 21 ] used aqueous extracts of Spirulina as a therapy for cytokine storm and reported a reduction of tumor necrosis factor (TNF)-α secretion levels induced by macrophage and monocyte. Anti-TNF therapy or TNF-α blockers are important to reduce inflammation-driven capillary leak caused by the key inflammatory cytokines which deteriorates the lung function of COVID-19 patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation